2020
DOI: 10.22270/jddt.v10i4.4167
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic Screening and Anti-inflammatory Investigation of the Methanol extract of stem bark of Blighia unijugata Baker (Sapindaceae)

Abstract: Introduction: Blighia unijugata is a potent medicinal plant extensively employed in traditional herbal remedies for the treatment of various diseases such as fever, fertility, inflammation, hypertension, migraine and treatment of infections due to microorganisms. Aim: This work, investigates the pharmacognostic screening and anti-inflammatory activities of the methanol extract of B. unijugata stem bark. Method: Collection, drying, pulverization, and methanol extraction of the stem bark were done ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Locally, it is used as a purgative, sedative, analgesic, antiemetic, anthelminthic, and for treating post-partum hemorrhage, vertigo, and boils [23][24][25] . The antimicrobial properties [26][27][28][29] , anti-oxidant activities [29][30][31] , cytotoxicity 28,30 , molluscicidal activity 32,33 , hypotensive effect 34,35 , antiinflammatory effect 36 , and anti-depressant properties 37 of Blighia unijugata have been studied in pre-clinical models. Its effect on total body weight 24,38 , estrogen, total protein, and total cholesterol 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Locally, it is used as a purgative, sedative, analgesic, antiemetic, anthelminthic, and for treating post-partum hemorrhage, vertigo, and boils [23][24][25] . The antimicrobial properties [26][27][28][29] , anti-oxidant activities [29][30][31] , cytotoxicity 28,30 , molluscicidal activity 32,33 , hypotensive effect 34,35 , antiinflammatory effect 36 , and anti-depressant properties 37 of Blighia unijugata have been studied in pre-clinical models. Its effect on total body weight 24,38 , estrogen, total protein, and total cholesterol 38 .…”
Section: Introductionmentioning
confidence: 99%
“…The wood of B. unijugata is commonly used for light construction, furniture, and charcoal production (Katende et al, 1995). Macroscopical investigation showed the stem bark outer layer is greyish and, the inner layer is pale reddish brown, with a disagreeable odor, while microscopical screening revealed the presence of starch grains, trichomes, and sclerenchyma and chemomicroscopic result revealed the presence of lignin, starch, calcium oxalate, cellulose, stone cells (Osuala, 2020). Significant inhibitory activity against the pathogenic microorganisms was observed when the nutritional elements, comparative study of the antimicrobial and cytotoxicity of the root, stem bark, and leaf essential oils, and crude extract of B. unijugata was investigated (Oderinde et al, 2008;Adewuyi, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Significant inhibitory activity against the pathogenic microorganisms was observed when the nutritional elements, comparative study of the antimicrobial and cytotoxicity of the root, stem bark, and leaf essential oils, and crude extract of B. unijugata was investigated (Oderinde et al, 2008;Adewuyi, et al, 2009). Phytochemical screening showed the presence of polyphenols, polyterpenes, and flavonoids while extract of the fruits and butanol fraction from the leaves of B. unijugata was reported not to be toxic in animal studies (Aquaisua et al, 2011;Bléyéré et al, 2013;Osuala, 2020). Hydrogen peroxide and DPPH free radical scavenging activities of leaf, stem bark, root, flower, and fruit of B. unijugata was reported by Ajiboye et al (2017a, b) and the essential oil compositions were reported (Dorcas et al, 2017) indicating the presence of terpenes.…”
Section: Introductionmentioning
confidence: 99%